Cutting of nonmetallic materials using ND:YAG laser beam - Ahmed Tahir, Bashir (2012)
This study deals with Nd:YAG laser cutting nonmetallic materials, which is one of the most important and popular industrial applications of laser. The main theme is to evaluate the effects of Nd:YAG laser beam power besides work piece scanning speed. For approximate cutting depth, a theoretical study is conducted in terms of material property and cutting speed. Results show a nonlinear relation between the cutting depth and input energy. There is no significant effect of speed on cutting depth with the speed being larger than 30 mm/s. An extra energy is utilized in the deep cutting. It is inferred that as the laser power increases, cutting depth increases. The experimental outcomes are in good agreement with theoretical results. This analysis will provide a guideline for laser-based industry to select a suitable laser for cutting, scribing, trimming, engraving, and marking nonmetallic materials.